PENGARUH PROGRAM SEMBAKO DAN PROGRAM KELUARGA HARAPAN TERHADAP KESEJAHTERAAN MASYARAKAT MISKIN MELALUI KONSUMSI RUMAH TANGGA - Agustini, Ni Luh Eka Sevia; Dewi, Ni Putu Martini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.06.TAHUN.2025DO - 10.24843/EEB.2025.v14.i06.p07, 2025)
Denpasar City faces complex socio-economic issues, particularly the high levels of poverty and income inequality, despite its role as the economic and administrative center of Bali Province. The government has responded to this condition through the implementation of the Program Sembako and the Program Keluarga Harapan (PKH) as forms of social assistance, which are expected to positively influence household consumption an important indicator of community welfare. The purpose of this study is to explain the role of household consumption in mediating the influence of Program Sembako and PKH on the welfare of the poor. This research uses a sample of 90 beneficiary families in Denpasar City, where questionnaire measurements are conducted using a psychometric scale (Likert), and analysis technique is path analysis. The study results indicate that Program Sembako and the PKH have a positive and significant effect on household consumption by 73.9%. Additionally, Program Sembako and the PKH, and household consumption positively and significantly influence the welfare of the poor by 79.9%. However, partially Program Sembako variable shows a negative and significant impact on the welfare of the poor. Program Sembako and the PKH have an indirect influence on the welfare of the poor through household consumption.